Race Matters: The “Aborigine” as a White Possession - Aileen Moreton-Robinson (2015)
Dictionaries are wonderful things. They help us understand meaning. In the everyday when we Indigenous people read the words “Aborigine/Aboriginal,” “Indian,” “Native,” we tend not to ask the question: What is their etymology? Instead we register at some level that these words have come to be connected to us. The word “aborigine” has its roots in Latin and in pre-Roman times referred to “from the beginning.” A few centuries later the English extended this meaning to refer to the original inhabitants of a country or region and is the most common use of the word outside of Australia. For example, the Aboriginal people of Canada homogenize three groups as descendants of the original inhabitants: Métis, Indians and Inuit. The Collins English Dictionary of 1979 denotes an Aboriginal as another word for an Aborigine which is defined as:— T h e “ A b o r i g i n e ” a s a W h i t e P o s s e s s i o n —Aborigine: 1. also called: native Australian (Austral) native (Austral) Black . a member of a dark-skinned hunting and gathering people who were living in Australia when European settlers arrived. Often shortened to Abo . 2. Any of the languages of this people. In this chapter I show that it is not our cultural densities by which we have been and are known by those who took our lands (Andersen 2009). Instead "race" is the predominant marker by which most of the colonizers' looking, speaking, and knowing has been and continues to be done in relation to the racialized Other.